救命a^2(b-c)+b^2(c-a)+c^2(a-b)

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/11 20:45:11
救命a^2(b-c)+b^2(c-a)+c^2(a-b)
x){6uӉ{4t5dDMd #Q7I&HģRΆHՔ -J2(6IHi`u$$9I`6 $2X4dݤd [)dؓ`g>rꜧz]d糷<[lcӮO',/.H̳ l';viӥXځͣO[Wl^tԧ{FF@Plu! oOv>koҋ_r: ҹZ:_ce<ka )^lݎ$

救命a^2(b-c)+b^2(c-a)+c^2(a-b)
救命
a^2(b-c)+b^2(c-a)+c^2(a-b)

救命a^2(b-c)+b^2(c-a)+c^2(a-b)
a²(b-c)+b²(c-a)+c²(a-b)
=a²b-a²c+b²c-ab²+c²a-c²b
=ab(a-b)-c(a+b)(a-b)+c²(a-b)
=(a-b)[ab-c(a+b)+c²]
=(a-b)[ab-ac-bc+c²]
=(a-b)[b(a-c)-c(a-c)]
=(a-b)(a-c)(b-c)
这位镜同学.你直接求助吧

楼主,您好

a²(b-c)+b²(c-a)+c²(a-b)
=a²b-a²c+b²c-ab²+c²a-c²b
=ab(a-b)-c(a+b)(a-b)+c²(a-b)
=(a-b)[ab-c(a+b)+c²]
=(a-b)[ab-ac-bc...

全部展开

楼主,您好

a²(b-c)+b²(c-a)+c²(a-b)
=a²b-a²c+b²c-ab²+c²a-c²b
=ab(a-b)-c(a+b)(a-b)+c²(a-b)
=(a-b)[ab-c(a+b)+c²]
=(a-b)[ab-ac-bc+c²]
=(a-b)[b(a-c)-c(a-c)]
=(a-b)(a-c)(b-c)
=-(a-b)(b-c)(c-a)
不懂,请追问,祝愉快O(∩_∩)O~

收起